Isolation, Identification and Characterisation of Bacterial species from Belepeh Waterfall, Sungai Iga, Sarawak - Stanley Sait, Agusti (Universiti Malaysia Sarawak (UNIMAS), 2018)
A waterfall is often associated with human activities as a recreational site, however, it is also a potential reservoir for waterborne disease-causing bacteria. Thus, the main aims of the study are to isolate and characterise the diverse bacteria species in the water sample collected from Belepeh waterfall. Bergey's Manual of Systematic Bacteriology was used to study the physiological properties of the bacteria species by performing biochemical identification such as Gram's staining, nitrate reduction test, oxidase and catalase test and selective media were used to differentiate between gram-positive and gram-negative bacteria. Meanwhile, molecular identification methods such as (GTG)--PCR and 16S rRNA PCR were used. Genetic fingerprinting using (GTG)s -PCR is a rapid, sensitive and specific in differentiation and identification of unknown bacterial isolates. In addition, GelJ software (v. 2.0) was used to construct dendrogram that shows genetic similarities and differences among the strains. Based on the result, six bacteria isolate from each different group are selected for further identification using 16S rRNA PCR. The PCR product from 16S rRNA PCR was sent to the Apical Scientific Laboratory Sdn. Bhd. for sequence analysis. The identities of bacteria after sequence analysis were Serratia marcescens, Acinetobacter baummani, Exiguobacterim indicum, Kocuria rhizophila, Bacillus spp., and Staphylococcus saprophyticus. Lastly, disc diffusion technique was used to analyse the antibiotic susceptibility of bacteria strains in which five out of six isolates showed MAR> 0.2 which mean that the isolates were recovered from slightly high-risk sources of contamination, while only one isolate showed MAR< 0.2, which mean that the bacteria isolate was recovered from low risk sources of contamination.